Effects of APOE ε4, age, and HIV on glial metabolites and cognitive deficits. - Chang, Linda; Jiang, Caroline; Cunningham, Eric; Buchthal, Steven; Douet, Vanessa; Andres, Marilou; Ernst, Thomas (Neurology, 2014)
Objective: We aimed to evaluate the combined effects of HIV and APOE ε4 allele(s) on glial metabolite levels, and on known cognitive deficits associated with either condition, across the ages.Methods: One hundred seventy-seven participants, primarily of white and mixed race (97 seronegative subjects: aged 44.7 ± 1.3 years, 85 [87.6%] men, 28 [28.9%] APOE ε4+; 80 HIV+ subjects: aged 47.3 ± 1.1 years, 73 [91.3%] men, 23 [28.8%] APOE ε4+), were assessed cross-sectionally for metabolite concentrations using proton magnetic resonance spectroscopy in 4 brain regions and for neuropsychological performance.Results: Frontal white matter myo-inositol was elevated in subjects with HIV across the age span but showed age-dependent increase in seronegative subjects, especially in APOE ε4+ carriers. In contrast, only seronegative APOE ε4+ subjects showed elevated myo-inositol in parietal cortex. All APOE ε4+ subjects had lower total creatine in basal ganglia. While all HIV subjects showed greater cognitive deficits, HIV+ APOE ε4+ subjects had the poorest executive function, fluency memory, and attention/working memory. Higher myo-inositol levels were associated with poorer fine motor function across all subjects, slower speed of information processing in APOE ε4+ subjects, and worse fluency in HIV+ APOE ε4+ subjects.Conclusions: In frontal white matter of subjects with HIV, the persistent elevation and lack of normal age-dependent increase in myo-inositol suggest that persistent glial activation attenuated the typical antagonistic pleiotropic effects of APOE ε4 on neuroinflammation. APOE ε4 negatively affects energy metabolism in brain regions rich in dopaminergic synapses. The combined effects of HIV infection and APOE ε4 may lead to greater cognitive deficits, especially in those with greater neuroinflammation. APOE ε4 allele(s) may be a useful genetic marker to identify white and mixed-race HIV subjects at risk for cognitive decline.